Long-Term Fishing Catch and Effort Trends in the Republic of the Marshall Islands, With Emphasis on the Small-Scale Sectors - Vianna, Gabriel M. S.; Hehre, E. James; White, Rachel; Hood, Lincoln; Derrick, Brittany; Zeller, Dirk (Frontiers in Marine Science, 2020)
Small-scale fishing has been an important element of the livelihood and food security in Pacific island countries throughout history; however, such catches have been under-reported in the official fisheries data. Here, we reconstruct the total domestic catches and fishing effort of the Republic of the Marshall Islands (RMI) by fishing sectors for 1950–2017. Reconstructed total catches were estimated to be 27% higher than the data officially reported by the Food and Agriculture Organization (FAO) of the United Nations on behalf of the RMI. Catches of the truly domestic, but export-oriented, industrial tuna sector accounted for 84% of the total catch, dominating catches since the early 2000s. The subsistence component contributed 74% of total small-scale catches, of which 92% was deemed unreported. The remaining 26% of small-scale catches were artisanal, i.e., small-scale commercial, in nature, of which 45% was deemed unreported. Trends suggested steady growth in small-scale catches from 1,100 t⋅year–1 in the early 1950s to a relatively stable level of 4,500 t⋅year–1 since the 1990s. However, over the 2009–2017 period, there was a gradual reduction of 2% per year in subsistence fishing, which was paralleled by a concomitant increase in artisanal catches of 3% per year. This gradual shift from predominantly non-commercial to commercial small-scale fisheries may be related to efforts to commercialize small-scale fisheries in the past decades. Small-scale fishing effort increased approximately 13-fold from the early 1980s to the late 2000s, stabilizing at around 401,000 kWdays since then, while catch-per-unit-of-effort (CPUE) displayed an inverse pattern, declining eightfold between the 1980s and 1990s, and stabilizing around 15 kg⋅kWdays–1 in recent decades. These findings may assist sustainable coastal fisheries management in the RMI, which is particularly important given the increasing impacts of climate change on local stocks.